2000
DOI: 10.1515/freq.2000.54.11-12.250
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Thick Film Ceramics for Tunable Microwave Coplanar Phase Shifters

Abstract: This paper introduces the processing and characterization of ferroelectric Barium-Strontium Titanate (BST) Ba^Sn-xTiOa thick film ceramics on AI 2 O 3 -microwave substrates. Applying a static interdigital capacitor model, the dielectric material properties of several different BST-thick films were determined by measurements of interdigital capacitors at 100 kHz and 1 MHz, and at room temperature of about 20 °C. Based upon different BSTthick films, microwave phase shifters in CoPlanar Waveguide (CPW) technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The lattice parameters of the calculated spectra were then matched against the JCPDS files (PDF numbers 79-2265, 34-0411, 44-0093, 39-1395 and 79-0175) to derive the Ba content x in Ba x Sr 1−x TiO 3 compounds [11]. In order to use this structural analysis, a few assumptions were made: (1) XRD peaks were considered as double peaks if their maximum did not coincide with their gravity centre, (2) Relative area under the calculated peaks S 1 /S 2 reflected the relative amount of the phases and (3) Vegard's law could be used for calculating x parameters of the phases. This method is suitable for qualitative analysis and not to be used as a quantitative analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lattice parameters of the calculated spectra were then matched against the JCPDS files (PDF numbers 79-2265, 34-0411, 44-0093, 39-1395 and 79-0175) to derive the Ba content x in Ba x Sr 1−x TiO 3 compounds [11]. In order to use this structural analysis, a few assumptions were made: (1) XRD peaks were considered as double peaks if their maximum did not coincide with their gravity centre, (2) Relative area under the calculated peaks S 1 /S 2 reflected the relative amount of the phases and (3) Vegard's law could be used for calculating x parameters of the phases. This method is suitable for qualitative analysis and not to be used as a quantitative analysis.…”
Section: Methodsmentioning
confidence: 99%
“…BST with a high dielectric constant and low dielectric loss finds application as capacitors [1]. BST with a reasonably low dielectric constant, low dielectric loss and high tunability is a potential candidate in phase shifters applications [2,3]. Recently, it was found that paraelectric BST has a potential to be used in microwave devices [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the values of ε r and tanδ, capacitance and loss measurements of interdigital capacitors (IDC) were carried out, as described in Ref. 13,6 .…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the values of ε r and tanδ, capacitance and loss measurements of interdigital capacitors (IDC) were carried out, as described in [15]. The IDC, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%